ДУХОВНО – НРАВСТВЕННОЕ ВОСПИТАНИЕ ГОСУДАРСТВЕННЫХ СЛУЖАЩИХ (Journal of actual problems of jurisprudence, 2019)
In this article author raises the problem of State employees’ cultural and moral education. Empowering State employees toprotect civil rights, freedoms and concerns, the society makes them not only legally, but morally responsible. According to author’sopinion this problem should be solved by training State employees and bringing up them to have sense of patriotism, responsibilityand professionalism.